MEKANISME GOOD CORPORATE GOVERNANCE DAN MANDATORY DISCLOSURE: STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ferry Diyanti (Faculty of Economics and Business Mulawarman University, 2013)
The research aims to find out the effect of Good Corporate Governance mechanism (consist of independent board of commisioner composition, independent audit committee composition, public ownership and managerial ownership) on the level of compliance to mandatory disclosure as according to regulation of BAPEPAM. This research use regulation of BAPEPAM No. SE-02/PM/2002 specially for manufacturing company. The researcg using data from 60 observations in the periods of 2007-2009. The research hypothesis were tested using the multiple regression analysis. This research find the effect of independent board of commisioner composition, independnet audit committee composition, public ownership and managerial ownership on the level compliance to mandatory disclosure as according to regulation of BAPEPAM.Â Keywords: Good Corporate Governance mechanism; mandatory disclosure